Impact of adjuvant chemotherapy for radically resected esophageal squamous cell carcinoma: a propensity score matching analysis - Chen, Shao-bin; Liu, Di-tian; Chen, Yu-ping (Frontiers in Surgery, 2023)
Background The aim of this study was to evaluate the impact of adjuvant chemotherapy in patients with radically resected esophageal squamous cell carcinoma (ESCC). Methods Patients with esophageal cancer who underwent esophagectomy at our hospital from 2010 to 2019 were retrospectively analyzed. Only patients with radically resected ESCC who did not receive neoadjuvant therapy or adjuvant radiotherapy were enrolled in this study. Propensity score matching (1:1) was used to balance the baseline. Results A total of 1,249 patients met the inclusion criteria and were enrolled in the study, and 263 patients received adjuvant chemotherapy. After matching, 260 pairs were analyzed. The 1-, 3-, and 5-year overall survival (OS) rates were 93.4%, 66.1% and 59.6%, respectively, for patients with adjuvant chemotherapy compared with 83.8%, 58.4% and 48.8%, respectively, for patients with surgery alone (P = 0.003). The 1-, 3-, and 5-year disease-free survival (DFS) rates were 82.3%, 58.8% and 51.3%, respectively, for patients with adjuvant chemotherapy compared with 68.0%, 48.3% and 40.8%, respectively, for patients with surgery alone (P = 0.002). In multivariate analyses, adjuvant chemotherapy was found to be an independent prognostic factor. In subgroup analyses, only the patients in certain subgroups were found to benefit from adjuvant chemotherapy, such as patients who underwent right thoracotomy, pT3 diseases, pN1-pN3 diseases, or pTNM stage III and IVA diseases. Conclusions Postoperative adjuvant chemotherapy can improve the OS and DFS of ESCC patients after radical resection but may only work for patients in certain subgroups.